Cultural orientation, perceived support and participation of female students in formal entrepreneurship in the sub-Saharan economy of Ghana. Issue 3 (17th July 2019) - Anlesinya, Alex; Adepoju, Oluwayemisi Ajoke; Richter, Ulf Henning
Abstract : Purpose: This purpose of this paper is to examine cultural orientations and intention of Ghanaian women to engage in entrepreneurship while assessing the role of perceived support system. The aim is to contribute to the literature in the sub-Saharan African context where women entrepreneurs are generally under-researched, despite their increasing significant roles in socio-economic development in the continent even in the face of huge cultural barriers. Design/methodology/approach: The study uses a hierarchical regression analysis and Hay's PROCESS moderation technique to analyze survey data from 190 female students from Ghana, Africa. Findings: The results indicate that uncertainty avoidance and power distance cultural orientations have significant positive and negative effects, respectively, on women's participation in formal entrepreneurship. However, collectivism and masculine cultural orientations do not have any effect on their intention to engage in formal entrepreneurial activity. The study further shows that perceived support system has a buffering effect on the destructive consequences of power distance culture on formal entrepreneurship intentions. On the contrary, perceived support does not moderate the relationship between uncertainty avoidance, collectivism and masculine cultural and formal entrepreneurial intention. Practical implications: Given the fact that most African governments are making efforts to accelerate the growth and development of their economies via entrepreneurship and economic empowerment, this study's findings encourage stakeholders to implement measures to leverage on the positive dimensions of cultures to facilitate the development of formal entrepreneurship among Ghanaian women while mitigating the negative consequences of cultural practices. The findings further highlight the need to evaluate the current level of support given to women in Ghana. The study suggests that provision of sufficient level of support can make women more willing to challenge the status quo in power distance cultures and take personal initiatives, thereby leading to more formal entrepreneurial actions. Originality/value: This study is a significant addition to women entrepreneurship literature because the role of culture in females' intention to participate in entrepreneurship is generally an under-researched area. Besides, our examination of national cultural variation at the individual level on formal entrepreneurship intention in a heterogeneous setting is novel. The study also highlights the buffering roles of perceived support on the destructive consequences of power distance cultural orientation on formal entrepreneurial development among women.